AKTIVITAS NGAYAH DALAM PERSEPSI PEREMPUAN HINDU BALI MASA KINI DI DESA ADAT BELEGA KECAMATAN BLAHBATUH KABUPATEN GIANYAR - Candra Kusuma, Kadek Mayuki Dwi; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
ABSTRACT This research examines the perception of contemporary Balinese Hindu women in viewing the obligation of ngayah in the Belega Traditional Village, Gianyar. The research method used is qualitative descriptive exploratory type. The theory is the structuration theory by Anthony Giddens. This theory explains that actors and structures have an inseparable duality relationship. Through the analysis carried out, positive perceptions of Balinese Hindu women emerged, followed by discursive awareness related to ngayah as a form of sincere yadnya. Practical awareness resulted in the emergence of negative perceptions related to ngayah as pressure from the traditional village structure. The type of women's public sector work affects their availability of time to sleep. The duality relationship that Giddens reveals between actors and structures is illustrated through the lives of Balinese Hindu women which cannot be separated from the traditional village structure that influences the perception of contemporary Balinese Hindu women in viewing ngayah. Keywords: ngayah, perception, Balinese Hindu women, structure and actor